Assessment of quality of life in women using Femelis Meno - Paszkowski, Tomasz; Skrzypulec-Plinta, Violetta (Menopause Review/Przegląd Menopauzalny, 2018)
Over 30% of women suffering from menopausal symptoms use products of plant origin. This paper presents the results of a study devoted to evaluation of the efficacy of the Femelis Meno dietary supplement containing standardized flower pollen and pistil extracts (PI 82-GC FEM).